« Il m’en souvient bien davantage » : pour une autre mémoire poétique de la fable « Philomèle et Progné » - Éva Avian (Itinéraires)
The myth of Philomela and Procne is often read in a way that associates literature with the function of telling what cannot be told. Interpreting the fable of La Fontaine “Philomel and Progne” using the concept of trauma leads to other definitions of poetry and its critics. The fable does not end up on a consolation. Its temporality is not related to recollections only. Its effect depends more on a certain style of transmission in which the reader feels rather than remembers a story yet already told. Thus, the fable opens the possibility of an experience deeply linked to the capacity to memorize.